Fine-tuning selective layer architecture of hydrogel membrane towards high separation performances for engineered osmosis - Qin, Detao (2020)
Ultrathin and/or ultrasmooth selective layer is one of the paramount goals in membrane realm for maximizing separation efficiency and/or minimizing fouling tendency. Towards this goal, the architecture of hydrogel selective layer is finely tuned for the first time for improving engineered osmosis (EO) membrane performance. Through delicately controlling synthesis parameters, ultrathin selective layer as thin as 30 nm, and ultrasmooth selective layer with sub-1 nm roughness (the smoothest EO membrane in literature) are successfully synthesized respectively. Analysis of reverse osmosis (RO) experimental results reveals hydrogel layer resistance to water permeation is linearly reduced by 1.40 × 1013 m−1 as the layer is tailored thinner per 10 nm, which leads to the remarkable enhancement of water permeability by ~10 times from 0.49 L m−2 h−1 bar−1 of 500 nm thickness to 4.75 L m−2 h−1 bar−1 of 30 nm thickness. Pressure-retarded osmosis (PRO) and forward osmosis (FO) tests indicate 45-nm-thick hydrogel layer achieves the maximum separation efficiency in terms of specific water flux (JW/JS). Moreover, the mechanism for tuning hydrogel layer architecture is discussed on the basis of microscopic characterizations. This study sheds new light on ultrathin and ultrasmooth selective layer for promoting EO membrane to smartly tackle different kinds of wastewater.